STRATEGI FUNDRAISING DANA ZAKAT DENGAN SISTEM QRIS DI BAZNAS KABUPATEN BANYUMAS - Miftaakhul Amri (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2022)
The purpose of this study is to see how far the implementation of the strategy of fundraising zakat funds using the QRIS system and how the flow of zakat payments through QRIS in BAZNAS Banyumas district. This research is a field research with a qualitative descriptive approach, and data collection is obtained from interviews and field observations. The results of the study show that the implementation of the fundraising and zakat strategy using QRIS at BAZNAS Banyumas goes through several stages, namely determining Muzakki's segments and targets, preparing human resources, building a communication system and compiling a service system. Not only that, BAZNAS Banyumas also runs a marketing communication strategy. That is by making interesting programs, creating feelings of empathy, collaborating with other companies, and providing the best service. To process zakat payments with QRIS, muzakki only need to scan the QR code for zakat payments at BAZNAS Banyumas, then follow the next payment steps. In a matter of minutes and without going to the BAZNAS Banyumas office, muzakki can pay their zakat whenever and wherever they are.